The Impact Of Quizizz-Assisted Problem-Based Learning (PBL) On Students' Learning Motivation And Problem-Solving Skills In Plane Geometry Topics Among Fourth-Grade Students At SDN Jatra Timur 1 Sampang - Lusy Ratnaningsih; Muhajir Muhajir; Sri Utami (Lembaga Riset dan Inovasi Almatani, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Quizizz media on students' learning motivation and problem-solving skills on the material of plane figures in grade IV of SDN Jatra Timur 1 Sampang. This study used a quantitative approach with a pre-experimental design of one group pretest-posttest. The research sample consisted of 40 fourth-grade students. Data collection techniques were carried out through questionnaires, observations, interviews, and documentation. Data analysis was carried out using normality tests and paired sample t-tests to test the significance of differences before and after treatment. The results showed that the application of the PBL model assisted by Quizizz media significantly increased students' learning motivation and problem-solving skills. This model was able to create an active, enjoyable learning atmosphere and encourage students to think critically and independently, in line with the demands of learning in the digital era.